Bernoulli differential equation
Divide both sides by "y^3"
To find the solution, change the dependent variable from y to z, where "z=y^{1-3}=y^{-2}"
"\\dfrac{-2}{y^3}\\dfrac{dy}{dx}-2y^{-2}=-2(\\cos x-\\sin x)"
"\\dfrac{dz}{dx}-2z=-2\\cos x+2\\sin x"
"P(x)=-2"
We have the integrating factor
Then multiplying through by "I(x)", we get
"\\dfrac{d}{dx}(e^{-2x}z)=2e^{-2x}(\\sin x-\\cos x)"
"e^{-2x}z=2\\int e^{-2x}(\\sin x-\\cos x)dx"
"\\int e^{-2x}\\sin xdx=-\\cos x e^{-2x}-2\\int e^{-2x}\\cos xdx"
"\\int e^{-2x}\\cos xdx=\\sin x e^{-2x}+2\\int e^{-2x}\\sin xdx"
"5\\int e^{-2x}\\sin xdx=-\\cos x e^{-2x}-2\\sin x e^{-2x}"
"\\int e^{-2x}\\sin xdx=-\\dfrac{1}{5}\\cos x e^{-2x}-\\dfrac{2}{5}\\sin x e^{-2x}"
"\\int e^{-2x}\\cos xdx=\\sin x e^{-2x}-\\dfrac{2}{5}\\cos x e^{-2x}-\\dfrac{4}{5}\\sin x e^{-2x}="
"=-\\dfrac{2}{5}\\cos x e^{-2x}+\\dfrac{1}{5}\\sin x e^{-2x}"
"+\\dfrac{4}{5}\\cos x e^{-2x}-\\dfrac{2}{5}\\sin x e^{-2x}+C="
"=\\dfrac{2}{5}\\cos x e^{-2x}-\\dfrac{6}{5}\\sin x e^{-2x}+C"
"z=\\dfrac{2}{5}\\cos x -\\dfrac{6}{5}\\sin x +Ce^{2x}"
"\\dfrac{1}{y^2}=\\dfrac{2}{5}\\cos x -\\dfrac{6}{5}\\sin x +Ce^{2x}"
"y^2=\\dfrac{1}{\\dfrac{2}{5}\\cos x -\\dfrac{6}{5}\\sin x +Ce^{2x}}"
Comments
Leave a comment